Analisis kesalahan siswa dalam memecahkan masalah soal cerita matematika materi skala ditinjau dari kecerdasan linguistik di sekolah dasar - Anggraheni Marsella Bella Astuti; Riyadi Riyadi; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2022)
Abstract. This research aims to describe the types and causes of errors students in solving math story problems on a fifth grade scale material in terms of linguistic intelligence uses a qualitative descriptive method with a case study. This research uses test and interview data collection techniques. Based on the results of the research, it can be concluded that the type of error students with high linguistic intelligence are errors in carry out the plans and errors in look back the answers because of inaccuracy in calculating math operations. Type the error of students with moderate linguistic intelligence is a mistaken devise a plan, carry out the plan, and look back the answers couse of the lack of ability in mathematical arithmetic operations and inaccuracy in writing the answer. The types of errors of students with linguistic intelligence low is an error in understanding the problem mistaken devise a plan, carry out the plan, and look back the answers because of the lack of ability read, Lack of ability in mathematical arithmetic operations, and look back the answers.